Ants of the genus Lordomyrma Emery (1) Generic synonymy, composition and distribution, with notes on Ancyridris Wheeler and Cyphoidris Weber (Hymenoptera: Formicidae: Myrmicinae) - Taylor, Robert W. (Zootaxa, 2009)
Synonymy under Lordomyrma of Prodicroaspis Emery and Promeranoplus Emery is reviewed. Lordomyrma currently comprises 25 named taxa, with two junior synonyms. Many undescribed species are known. Relative levels of species richness and morphological diversity are compared for the SE Asian/Japanese, Australian, Melanesian, New Caledonian and Fijian Lordomyrma faunas. Twelve species, including examples of the related genera Ancyridris and Cyphoidris are illustrated. The need for conservation and study of the remarkable, threatened ant faunas of New Caledonia, New Guinea and Fiji is discussed, and the relative positions of Ancyridris and Cyphoidris reviewed.